Single‐nucleotide substitution of Hepatitis B virus in intrauterine infection. Issue 4 (29th October 2014) - Wang, L.‐J.; Xu, Y.‐F.; Liu, X.‐X.; Chen, Y.
Summary The relationship between hepatitis B virus (HBV) gene polymorphism and intrauterine infection has not been completely illuminated. Six pairs of mother and infant from intrauterine infection group and six mothers from nonintrauterine infection group in the previous study were randomly selected and separately divided into group M (Mother group), group N (Neonate group) and group NM (Negative‐mother group) in this study. We found that age, gestational weeks, HBsAg titre, HBeAg titre and HBV DNA level of mothers from group M and group NM were not significantly different. Pre‐S1/S2 and S regions in HBV genome were amplified, inserted into pUC19 plasmid and sequenced. It was found that all clone sequences clustered into genotype C (AY123041) through the Genotyping tool in NCBI and phylogenetic trees. Compared with AY123041, there were 20 (11 plus 9) mutations significantly different in the three groups. Most of the mutations were synonymous in pre‐S1/S2/S region, while mutations of C2990T, T3205A, A167G, C407A, A667T and A680C resulted in amino acid substitution of A90V, S162T, T47A, P127T, L213F and I218L, respectively. In addition, most of the 20 mutations caused amino acid substitution in polymerase region for the tight structure of HBV genome. The occurrence and location of mutations indicated that mutation of C2990T only existing in group NM may serve as an index for nonintrauterine infection. In contrast, the incidence of intrauterine HBV infection from mothers with mutation of T3205A was lower. Then, mutations of G403A, T670G, A673G, A167G, C407A, A667T and A680C may be closely related to intrauterine HBV infection.